Thermal Effects during Bone Preparation and Insertion of Osseointegrated Transfemoral Implants - Emir Benca; Beatrice Ferrante; Martin Zalaudek; Lena Hirtler; Alexander Synek; Franz M. Kainberger; Reinhard Windhager; Rickard Brånemark; Gerhard M. Hobusch; Ewald Unger (Sensors, 2021)
Background: The preparation of bone for the insertion of an osseointegrated transfemoral implant and the insertion process are performed at very low speeds in order to avoid thermal damages to bone tissue which may potentially jeopardize implant stability. The aim of this study was to quantify the temperature increase in the femur at different sites and insertion depths, relative to the final implant position during the stepwise implantation procedure. Methods: The procedure for installation of the osseointegrated implant was performed on 24 femoral specimens. In one specimen of each pair, the surgery was performed at the clinically practiced speed, while the speed was doubled in the contralateral specimen. Six 0.075 mm K fine gauge thermocouples (RS Components, Sorby, UK) were inserted into the specimen at a distance of 0.5 mm from the final implant surface, and six were inserted at a distance of 1.0 mm. Results: Drilling caused a temperature increase of <2.5 °C and was not statistically significantly different for most drill sizes (0.002 < p < 0.845). The mean increase in temperature during thread tapping and implant insertion was <5.0 °C, whereas the speed had an effect on the temperature increase during thread tapping. Conclusions: Drilling is the most time-consuming part of the surgery. Doubling the clinically practiced speed did not generate more heat during this step, suggesting the speed and thus the time- and cost-effectiveness of the procedure could be increased. The frequent withdrawal of the instruments and removal of the bone chips is beneficial to prevent temperature peaks, especially during thread tapping.